2014
DOI: 10.1093/database/bau047
|View full text |Cite
|
Sign up to set email alerts
|

'RetinoGenetics': a comprehensive mutation database for genes related to inherited retinal degeneration

Abstract: Inherited retinal degeneration (IRD), a leading cause of human blindness worldwide, is exceptionally heterogeneous with clinical heterogeneity and genetic variety. During the past decades, tremendous efforts have been made to explore the complex heterogeneity, and massive mutations have been identified in different genes underlying IRD with the significant advancement of sequencing technology. In this study, we developed a comprehensive database, ‘RetinoGenetics’, which contains informative knowledge about all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The key neuronal cell type that undergoes degeneration in most inherited forms of blindness is the cone photoreceptor, which mediates high-acuity and color vision (26). Such inherited diseases are genetically heterogeneous, with at least 60 loci identified in humans for RP, one of the more common forms of inherited blindness (27). Most of the RP genes primarily or exclusively affect the rod photoreceptor, which mediates vision in low light conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key neuronal cell type that undergoes degeneration in most inherited forms of blindness is the cone photoreceptor, which mediates high-acuity and color vision (26). Such inherited diseases are genetically heterogeneous, with at least 60 loci identified in humans for RP, one of the more common forms of inherited blindness (27). Most of the RP genes primarily or exclusively affect the rod photoreceptor, which mediates vision in low light conditions.…”
Section: Resultsmentioning
confidence: 99%
“…There is exceptional genetic heterogeneity associated with retinal degeneration diseases, with approximately 200 disease genes and thousands of mutations identified in humans leading to blindness (27). Addressing each genetic deficit would be a dif- Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…There is great heterogeneity underlying retinal degenerative diseases. Thousands of mutations in >200 genes have been identified that lead to blindness in humans (2). In developing therapeutic strategies to treat blindness, it may not be practical to target each genetic defect; however targeting common disease mechanisms holds promise for the development of realistic treatment for patients suffering from retinal disease.…”
mentioning
confidence: 99%
“…To date, more than 250 disease-causing genes and 4000 different mutations have been identified in multiple phenotypes of IRDs (RetNet; https://sph.uth.edu/retnet/home.htm, in the public domain). 5,6 Among these identified IRD genes, the top leading ones include USH2A, EYS, ABCA4, PDE6B, RPGR, and RHO. [7][8][9][10][11][12][13] However, a definitive molecular diagnosis of IRD remains extremely complex and challenging because mutations are only detected in 40% to 60% of cases.…”
mentioning
confidence: 99%